2009
DOI: 10.1080/17482940903003000
|View full text |Cite
|
Sign up to set email alerts
|

Massive coronary perforation and shock: From appropriate labeling to appropriate calls

Abstract: Coronary perforation is a rare, unpredictable and dreaded complication of percutaneous coronary Intervention. With Ellis Grade 3 perforations the only effective treatment includes temporary balloon occlusion of the perforated coronary artery and placement of JOSTENT GraftMaster stent to cover the perforation. The authors describe coronary perforation during proximal right coronary artery (RCA) stenting, resulting in immediate cardiogenic shock. The patient was treated with temporary balloon occlusion of the RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Kalusky et al . [38] reported that GraftMasters of ≤5 mm can be easily deployed via 6 Fr guiding catheters as demonstrated in these two patients. In a recent study, treating a coronary artery perforation with two guide catheters through dual access enabled a rapid delivery of covered stent or coils to the vessel, without losing control of the perforation site.…”
Section: Discussionmentioning
confidence: 80%
“…Kalusky et al . [38] reported that GraftMasters of ≤5 mm can be easily deployed via 6 Fr guiding catheters as demonstrated in these two patients. In a recent study, treating a coronary artery perforation with two guide catheters through dual access enabled a rapid delivery of covered stent or coils to the vessel, without losing control of the perforation site.…”
Section: Discussionmentioning
confidence: 80%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…GraftMaster Coronary Stent Graft System is approved under Humanitarian Device Exemption for the repair of free perforations in native coronary vessels and SVG. There are some reported cases of repair of native coronary artery aneurysms and perforations with GraftMaster [10-11]. However, it has been rarely used for the repair of SVG pseudoaneurysms [12].…”
Section: Discussionmentioning
confidence: 99%